Context as a Dynamic Construct and the Problem of Context Sensitivity - Kozubíková Šandová, Jana (Wiley-Blackwell, 2019)
This paper is concerned with different aspects of the concept of context, predominantly from the perspective of contemporary pragmatically‐oriented linguistics. As it is frequently claimed that the precise meaning of an utterance may be determined correctly only in context, but, at the same time, no agreement has been reached on how context should be adequately defined, one aim of this study is to focus on different characteristics of this phenomenon and to explain how context may be best understood within a pragmatic approach. This is connected with context sensitivity. Some expressions in natural language are prototypical examples of it, while others are rather controversial. The other aim of this study is to examine context sensitivity from the point of view of several semantic theories and to propose within which systematic linguistic theory it could be best integrated. It turns out that the concept of context should best be treated as a dynamic construct inherently connected with communication. Since it is, at the same time, a multilayered concept, it is almost impossible to produce a widely acceptable theory of context. Regarding a systematic theory within which context sensitivity could be integrated, semantic minimalism seems to be the most appropriate.
Kontext jako dynamický konstrukt a problematika kontextové závislosti
Keywords: context; context sensitivity; context-dependent expressions; semantic minimalism; radical contextualism; kontext; kontextová závislost; kontextově závislé výrazy; sémantický minimalismus; radikální kontextualismus